172 A Slow-Releasing Synthetic Prostacyclin Agonist â€œOno 1301-srâ€ Combined with Omental Flap Increases Myocardial Blood Flow and Reduces Microvascular Resistance, Associated with Functional Recovery, in a Porcine Chronic Myocardial Infarction Model. (3rd June 2016) - Yajima, Shin; Miyagawa, Shigeru; Fukushima, Satsuki; Sakai, Yoshiki; Harada, Akima; Isohashi, Kayako; Watabe, Tadashi; Ikeda, Hayato; Horitsugi, Genki; Hatazawa, Jun; Sawa, Yoshiki
Abstract : Introduction: Coronary microvascular dysfunction (MVD) has been shown to be the major cause of persistent myocardial ischaemia and progressive left ventricular (LV) remodelling in the chronic myocardial infarction (MI) heart. ONO-1301SR is a slow-releasing synthetic prostacyclin agonist, being developed to induce angiogenesis by upregulating a variety of proangiogenic cytokines in the targeted region. In addition, pedicle omental flap covering over the LV surface reportedly yields proangiogenic effects on chronic MI heart. We herein hypothesised pedicle omental flap covering, combined with ONO-1301SR placement. over the LV surface may be effective on the MVD and related functional deterioration in a chronic MI heart. To test this hypothesis, clinically latest imaging studies were applied in a porcine chronic MI model. Methods: A mini-pig chronic MI model was generated by placing an ameroid constrictor around the left anterior descending artery for 4 weeks. The mini-pigs were then randomly assigned into the following 4 groups; sham group, omental flap alone (OM group), ONO-1301SR alone (ONO group), ONO-1301SR plus omental flap (ONO+OM group, n = 6 each). Results: At 4 weeks after the treatment, 13 N-ammonia PET study showed that the ONO+OM group, but not the other groups, displayed a significantly increase in myocardial blood flow (189 ± 89% increase, P < 0.05) and coronary flow reserve (179 ± 121% increase, P < 0.05) under the stress compared to those under the rest. This trend was predominated in the left circumflex territory. In addition, coronary angiogram and pressure-temperature sensor wire study showed that the ONO+OM and the ONO groups, but not the OM group, showed a significantly greater number of collateral arteries and smaller indexed of microvascular resistance, in particular, in the left circumflex territory, compared to the sham group. Moreover, echocardiographical EF was significantly greater in the ONO+OM group (50 ± 7%) and the ONO group (48 ± 3%), compared to the OM group (41 ± 3%) and the sham group (38 ± 5%) at 4 weeks. Furthermore, histological density of CD31-positive capillaries and CD31SMA-double positive arterioles were significantly greater in the ONO+OM group than the sham group or the OM group, in association with a significantly smaller myocyte size and interstitial fibrous area in the ONO+OM and the ONO group compared to those in the other groups. However, expression of proangiogenic cytokines, such as vascular endothelial growth factor, hepatocyte growth factor or stem cell-derived factor-1, were not significantly different among the groups, indicating that angiogenic process might have been completed at the 4 weeks after the treatment. Conclusions: ONO-1301SR combined with omental flap therapy promoted myocardial angiogenesis with collateral artery growth, leading to recovery of the cardiac function in a porcine ICM model. This combined therapy may be useful in regenerating myocardial microvasculature.